Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Corrigendum to “Substantial increases in burned area in circumboreal forests from 1983 to 2020 captured by the AVHRR record and a new autoregressive burned area detection algorithm” [Remote Sensing of Environment 325(2025) 114789] - Connor W. Stephens; Anthony R. Ives; Volker C. Radeloff (Remote Sensing of Environment, 2026)

A phase I clinical study to evaluate rapid, high-volume, subcutaneous auto-injector tolerability with recombinant human hyaluronidase - David W. Kang; Robert J. Connor; Tara Nekoroski; Jo Ann M. Bitsura; Susan K. Kindig; Stephen P. Knowles; Michael J. LaBarre (Drug Delivery and Translational Research, 2026)
Until recently, approved handheld auto-injectors (AIs) have been limited to volumes ≤ 2 mL. A prototype rapid high-volume AI (HVAI) that can deliver 10 mL in 30 s was developed to administer therapeutics co-formulated with a proprietary recombinant human hyaluronidase PH20 (rHuPH20). This phase I, open-label study assessed the tolerability of subcutaneous (SC) injections of 10% (100 mg/mL) immunoglobulin G (IgG) solution co-administered with 4000 U/mL rHuPH20, delivered using a syringe pump at a target rate of 5 or 10 mL/30 seconds or the prototype HVAI at a target rate of 10 mL/30 seconds in healthy human subjects. Subjects received 5 mL (Cohort A, n = 12) or 10 mL (Cohort B, n = 12) of test solution via syringe pump (injection visit 1), and 10 mL of test solution via HVAI (Cohorts A & B; injection visit 2). Primary endpoints were tolerability and safety outcomes. Secondary endpoints included HVAI injection duration. All 24 subjects completed visit 1; 23/24 completed visit 2. All injections were tolerated, with no serious adverse events (AEs). Following syringe pump administration, 6/24 subjects (25%) reported eight treatment-emergent AEs (TEAEs); after HVAI administration, 4/23 (17%) reported four TEAEs, all mild in severity. Mean (± SEM) injection duration via HVAI was 27.9 ± 0.8 s. Most subjects (91%, 21/23) experienced no or mild injection-site pain following HVAI administration, and 96% (22/23) said they would be willing to have the HVAI injection again. SC injection of a 10% IgG solution in combination with rHuPH20 was well tolerated at an injection rate of 10 mL/~30 s using the prototype HVAI.

Combining analysis of individual and wastewater whole genome sequencing improves SARS-CoV-2 surveillance - Evan P. Troendle; Andrew J. Lee; Marina I. Reyne; Danielle M. Allen; Stephen J. Bridgett; Clara H. Radulescu; Michael Glenn; John-Paul Wilkins; Francesco Rubino; Behnam Firoozi Nejad; Cormac McSparron; Marc Niebel; et al. (Water Research, 2025)

Substantial increases in burned area in circumboreal forests from 1983 to 2020 captured by the AVHRR record and a new autoregressive burned area detection algorithm - Connor W. Stephens; Anthony R. Ives; Volker C. Radeloff (Remote Sensing of Environment, 2025)

Embracing social-ecological system complexity to promote climate-ready fisheries - Chris J. Harvey; Patricia M. Clay; Rebecca Selden; Stephanie K. Moore; Kelly S. Andrews; Yvonne L. deReynier; Anne H. Beaudreau; Owen R. Liu; Karma C. Norman; Jameal F. Samhouri; Lyall Bellquist; Merrick Burden; et al. (Reviews in Fish Biology and Fisheries, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Development and in-vitro assessment of novel oxygen-releasing feed additives to reduce enteric ruminant methane emissions - Alison Graham; Camilla Thorn; Michael McDonagh; Caroline O'Donnell; Stephen Nolan; Stuart F. Kirwan; Sandra O'Connor; Corine O. Nzeteu; Alejandra C.V. Montoya; Andrew Bartle; Alison Hall; Cathy Abberton; et al. (Science of The Total Environment, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Population dynamics of the Lyme disease bacterium, Borrelia burgdorferi , during rapid range expansion in New York State - Zachary J. Oppler; Melissa A. Prusinski; Kayleigh R. O'Keeffe; Patrick Pearson; Stephen M. Rich; Richard C. Falco; Vanessa Vinci; Collin O'Connor; Jamie Haight; P. Bryon Backenson; Dustin Brisson (Molecular Ecology, 2024)
Recent changes in climate and human land‐use have resulted in alterations of the geographic range of many species, including human pathogens. Geographic range expansion and population growth of human pathogens increase human disease risk. Relatively little empirical work has investigated the impact of range changes on within‐population variability, a contributor to both colonization success and adaptive potential, during the precise time in which populations are colonized. This is likely due to the difficulties of collecting appropriate natural samples during the dynamic phase of migration and colonization. We systematically collected blacklegged ticks ( Ixodes scapularis ) across New York State (NY), USA, between 2006 and 2019, a time period coinciding with a rapid range expansion of ticks and their associated pathogens including Borrelia burgdorferi , the etiological agent of Lyme disease. These samples provide a unique opportunity to investigate the population dynamics of human pathogens as they expand into novel territory. We observed that founder effects were short‐lived, as gene flow from long‐established populations brought almost all B. burgdorferi lineages to newly colonized populations within just a few years of colonization. By 7 years post‐colonization, B. burgdorferi lineage frequency distributions were indistinguishable from long‐established sites, indicating that local B. burgdorferi populations experience similar selective pressures despite geographic separation. The B. burgdorferi lineage dynamics elucidate the processes underlying the range expansion and demonstrate that migration into, and selection within, newly colonized sites operate on different time scales.

Trends in prescribed fire weather windows from 2000 to 2022 in California - Christina A. Fossum; Brandon M. Collins; Connor W. Stephens; Jamie M. Lydersen; Joe Restaino; Taj Katuna; Scott L. Stephens (Forest Ecology and Management, 2024)

Impact of locational pricing on the roll out of heat pumps in the UK - Andrew Lyden; Samuel Alene; Peter Connor; Renaldi Renaldi; Stephen Watson (Energy Policy, 2024)

Original plant diversity and ecosystems of a small, remote oceanic island (Corvo, Azores): Implications for biodiversity conservation - Simon E. Connor; Tara Lewis; Jacqueline F.N. van Leeuwen; W.O. (Pim) van der Knaap; Hanno Schaefer; Nicholas Porch; Ana I. Gomes; Stephen B. Piva; Patricia Gadd; Petr Kuneš; Simon G. Haberle; Matthew A. Adeleye; et al. (Biological Conservation, 2024)

Flow induced attrition of cellulose nanocrystals - Bradley P. Sutliff; Connor Farrell; Stephen M. Martin; Michael J. Bortner (Carbohydrate Polymers, 2023)

Pseudomonas umsongensis GO16 as a platform for the in vivo synthesis of short and medium chain length polyhydroxyalkanoate blends - Federico Cerrone; Binbin Zhou; Agathe Mouren; Luc Avérous; Stephen Conroy; Jeremy C. Simpson; Kevin E. O'Connor; Tanja Narancic (Bioresource Technology, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Exploratory analysis of machine learning techniques in the Nevada geothermal play fairway analysis - Connor M. Smith; James E. Faulds; Stephen Brown; Mark Coolbaugh; Jacob DeAngelo; Jonathan M. Glen; Erick R. Burns; Drew L. Siler; Sven Treitel; Eli Mlawsky; Michael Fehler; Chen Gu; et al. (Geothermics, 2023)

Spiral Laminar Flow is Associated with a Reduction in Disturbed Shear in Patient-Specific Models of an Arteriovenous Fistula - Connor V. Cunnane; J. Graeme Houston; Daniel T. Moran; Stephen P. Broderick; Rose A. Ross; Michael T. Walsh (Cardiovascular Engineering and Technology, 2023)

Detection of human adenovirus F41 in wastewater and its relationship to clinical cases of acute hepatitis of unknown aetiology - Marina I. Reyne; Danielle M. Allen; Ashley Levickas; Pearce Allingham; Jonathan Lock; Arthur Fitzgerald; Cormac McSparron; Behnam F. Nejad; Jennifer McKinley; Andrew Lee; Stephen H. Bell; Joshua Quick; et al. (Science of The Total Environment, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Quantifying drivers of change in social-ecological systems: land management impacts wildfire probability in forests of the western US - Katherine J. Siegel; Laurel Larsen; Connor Stephens; William Stewart; Van Butsic (Regional Environmental Change, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Assessing Long-Term Ecological Changes in Wetlands of the Bass Strait Islands, Southeast Australia: Palaeoecological Insights and Management Implications - Matthew Adesanya Adeleye; Simon Graeme Haberle; Stephen Harris; Simon Edward Connor; Janelle Stevenson (Wetlands, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Does getting defensive get you anywhere?—Seasonal balancing selection, temperature, and parasitoids shape real‐world, protective endosymbiont dynamics in the pea aphid - Andrew H. Smith; Michael P. O’Connor; Brooke Deal; Coleman Kotzer; Amanda Lee; Barrett Wagner; Jonah Joffe; Stephen Woloszynek; Kerry M. Oliver; Jacob A. Russell (Molecular Ecology, 2021)
Facultative, heritable endosymbionts are found at intermediate prevalence within most insect species, playing frequent roles in their hosts’ defence against environmental pressures. Focusing on Hamiltonella defensa , a common bacterial endosymbiont of aphids, we tested the hypothesis that such pressures impose seasonal balancing selection, shaping a widespread infection polymorphism. In our studied pea aphid ( Acyrthosiphon pisum ) population, Hamiltonella frequencies ranged from 23.2% to 68.1% across a six‐month longitudinal survey. Rapid spikes and declines were often consistent across fields, and we estimated that selection coefficients for Hamiltonella ‐infected aphids changed sign within this field season. Prior laboratory research suggested antiparasitoid defence as the major Hamiltonella benefit, and costs under parasitoid absence. While a prior field study suggested these forces can sometimes act as counter‐weights in a regime of seasonal balancing selection, our present survey showed no significant relationship between parasitoid wasps and Hamiltonella prevalence. Field cage experiments provided some explanation: parasitoids drove modest ~10% boosts to Hamiltonella frequencies that would be hard to detect under less controlled conditions. They also showed that Hamiltonella was not always costly under parasitoid exclusion, contradicting another prediction. Instead, our longitudinal survey – and two overwintering studies – showed temperature to be the strongest predictor of Hamiltonella prevalence. Matching some prior lab discoveries, this suggested that thermally sensitive costs and benefits, unrelated to parasitism, can shape Hamiltonella dynamics. These results add to a growing body of evidence for rapid, seasonal adaptation in multivoltine organisms, suggesting that such adaptation can be mediated through the diverse impacts of heritable bacterial endosymbionts.

Holocene heathland development in temperate oceanic Southern Hemisphere: Key drivers in a global context - Matthew Adesanya Adeleye; Simon Graeme Haberle; Stephen Harris; Felicitas Viktoria‐Louise Hopf; Simon Connor; Janelle Stevenson (Journal of Biogeography, 2021)
Aim Understanding long‐term heathland development is key in mitigating their current attrition globally. However, such knowledge is limited in Australia and the wider Southern Hemisphere. We aim to identify potential climatic and environmental drivers of Holocene heathland development in temperate‐oceanic Australia (Bass Strait), and also assess the applicability of Iversen's conceptual model of interglacial vegetation development to the area. Location Bass Strait, southeast Australia. Taxon Monotoca, Epacris, Sprengelia and Restionaceae. Methods We used multiple sedimentary pollen and charcoal records from truwana/Cape Barren Island (CBI) in Bass Strait to reconstruct vegetation and fire history. We also used rarefaction analysis on pollen records to estimate floristic richness for all sites, and magnetic susceptibility and organic content were derived for two of the four sites as proxies for local sedimentary changes. Reconstructed vegetation and fire histories were then compared to independent records of climate and sea‐level change in temperate Australia, using a Detrended Correspondence Analysis ordination, to identify major drivers of heathland development. Results Major heathland expansion occurred on truwana/CBI between the early and mid‐Holocene in response to sea‐level rise, high effective precipitation, reduced seasonality and increased Indigenous burning. Increasing seasonality, low effective precipitation, El Niño‐Southern Oscillation intensification, stable sea level, and decreased fire activity drove the expansion of scrub and woodland at the expense of heathland in the late Holocene. The overall vegetation development on truwana/CBI fits poorly with the classic Iversen conceptual model of interglacial vegetation development in the Northern Hemisphere, due to the significant role of interglacial sea‐level rise on truwana/CBI. Therefore, a modified model, which takes into account the role of sea‐level change, is proposed for Southern Hemisphere‐temperate‐oceanic settings. Main conclusions Heathland developments in both hemispheres reflect some level of homogeneity, considering the roles of increased Indigenous burning and reduced seasonality in both hemispheres. Frequent, controlled burning strategies are recommended to maintain heathland on truwana/CBI.

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Light-Weight Portable Electroantennography Device as a Future Field-Based Tool for Applied Chemical Ecology - Stephen M. Pawson; Jessica L. Kerr; Brooke C. O’Connor; Philippe Lucas; Dominique Martinez; Jeremy D. Allison; Tara M. Strand (Journal of Chemical Ecology, 2020)

Impacts of land management practices on blue carbon stocks and greenhouse gas fluxes in coastal ecosystems—A meta‐analysis - J. Jack O’Connor; Benedikt J. Fest; Michael Sievers; Stephen E. Swearer (Global Change Biology, 2020)
Global recognition of climate change and its predicted consequences has created the need for practical management strategies for increasing the ability of natural ecosystems to capture and store atmospheric carbon. Mangrove forests, saltmarshes and seagrass meadows, referred to as blue carbon ecosystems (BCEs), are hotspots of atmospheric CO 2 storage due to their capacity to sequester carbon at a far higher rate than terrestrial forests. Despite increased effort to understand the mechanisms underpinning blue carbon fluxes, there has been little synthesis of how management activities influence carbon stocks and greenhouse gas (GHG) fluxes in BCEs. Here, we present a global meta‐analysis of 111 studies that measured how carbon stocks and GHG fluxes in BCEs respond to various coastal management strategies. Research effort has focused mainly on restoration approaches, which resulted in significant increases in blue carbon after 4 years compared to degraded sites, and the potential to reach parity with natural sites after 7–17 years. Lesser studied management alternatives, such as sediment manipulation and altered hydrology, showed only increases in biomass and weaker responses for soil carbon stocks and sequestration. The response of GHG emissions to management was complex, with managed sites emitting less than natural reference sites but emitting more compared to degraded sites. Individual GHGs also differed in their responses to management. To date, blue carbon management studies are underrepresented in the southern hemisphere and are usually limited in duration (61% of studies

Conserving the abundance of nonthreatened species - David J. Baker; Stephen T. Garnett; James O'Connor; Glenn Ehmke; Rohan H. Clarke; John C.Z. Woinarski; Melodie A. McGeoch (Conservation Biology, 2019)
Human modification of the environment is driving declines in population size and distributional extent of much of the world's biota. These declines extend to many of the most abundant and widespread species, for which proportionally small declines can result in the loss of vast numbers of individuals, biomass, and interactions. These losses could have major localized effects on ecological and cultural processes and services without elevating a species’ global extinction risk. Although most conservation effort is directed at species threatened with extinction in the very near term, the value of retaining abundance regardless of global extinction risk is justifiable based on many biodiversity or ecosystem service metrics, including cultural services, at scales from local to global. The challenges of identifying conservation priorities for widespread and abundant species include quantifying the effects of species’ abundance on services and understanding how these effects are realized as populations decline. Negative effects of population declines may be disconnected from the threat processes driving declines because of species movements and environment flows (e.g., hydrology). Conservation prioritization for these species shares greater similarity with invasive species risk assessments than extinction risk assessments because of the importance of local context and per capita effects of abundance on other species. Because conservation priorities usually focus on preventing the extinction of threatened species, the rationale and objectives for incorporating declines of nonthreatened species must be clearly articulated, going beyond extinction risk to encompass the range of likely harmful effects (e.g., secondary extinctions, loss of ecosystem services) if declines persist or are not reversed. Research should focus on characterizing the effects of local declines in species that are not threatened globally across a range of ecosystem services and quantifying the spatial distribution of these effects through the distribution of abundance. The case for conserving abundance in nonthreatened species can be made most powerfully when the costs of losing this abundance are better understood.

Enhancing National Climate Services (ENACTS) for development in Africa - Tufa Dinku; Madeleine C. Thomson; Rémi Cousin; John del Corral; Pietro Ceccato; James Hansen; Stephen J. Connor (Climate and Development, 2018)

Effects of multiple climate change stressors: ocean acidification interacts with warming, hyposalinity, and low food supply on the larvae of the brooding flat oyster Ostrea angasi - Victoria J. Cole; Laura M. Parker; Stephen J. O’Connor; Wayne A. O’Connor; Elliot Scanes; Maria Byrne; Pauline M. Ross (Marine Biology, 2016)

Advancing Product Quality: a Summary of the Second FDA/PQRI Conference - Lawrence X. Yu; Ilgaz Akseli; Barbara Allen; Gregory Amidon; Tara Gooen Bizjak; Ashley Boam; Margaret Caulk; David Doleski; Joseph Famulare; Adam C. Fisher; Scott Furness; Brian Hasselbalch; et al. (The AAPS Journal, 2016)

Genetic and platelet function testing of antiplatelet therapy for percutaneous coronary intervention: the ARCTIC-GENE study - Jean-Philippe Collet; Jean-Sébastien Hulot; Thomas Cuisset; Grégoire Rangé; Guillaume Cayla; Eric Van Belle; Simon Elhadad; Hélène Rousseau; Pierre Sabouret; Stephen A. O’Connor; Jérémie Abtan; Mathieu Kerneis; et al. (European Journal of Clinical Pharmacology, 2015)

Prasugrel but not high dose clopidogrel overcomes the lansoprazole neutralizing effect of P2Y12 inhibition: Results of the randomized DOSAPI study - Jean-Philippe Collet; Jean-Sébastien Hulot; Jérémie Abtan; Ghalia Anzaha; Mathieu Kerneis; Johanne Silvain; Guillaume Cayla; Stephen A. O’Connor; Olivier Barthélémy; Farzin Beygui; Sophie Galier; Delphine Brugier; et al. (European Journal of Clinical Pharmacology, 2014)

Combined use of satellite estimates and rain gauge observations to generate high‐quality historical rainfall time series over Ethiopia - Tufa Dinku; Kinfe Hailemariam; Ross Maidment; Elena Tarnavsky; Stephen Connor (International Journal of Climatology, 2014)
Climate data are used in a number of applications including climate risk management and adaptation to climate change. However, the availability of climate data, particularly throughout rural Africa, is very limited. Available weather stations are unevenly distributed and mainly located along main roads in cities and towns. This imposes severe limitations to the availability of climate information and services for the rural community where, arguably, these services are needed most. Weather station data also suffer from gaps in the time series. Satellite proxies, particularly satellite rainfall estimate, have been used as alternatives because of their availability even over remote parts of the world. However, satellite rainfall estimates also suffer from a number of critical shortcomings that include heterogeneous time series, short time period of observation, and poor accuracy particularly at higher temporal and spatial resolutions. An attempt is made here to alleviate these problems by combining station measurements with the complete spatial coverage of satellite rainfall estimates. Rain gauge observations are merged with a locally calibrated version of the TAMSAT satellite rainfall estimates to produce over 30‐years (1983‐todate) of rainfall estimates over Ethiopia at a spatial resolution of 10 km and a ten‐daily time scale. This involves quality control of rain gauge data, generating locally calibrated version of the TAMSAT rainfall estimates, and combining these with rain gauge observations from national station network. The infrared‐only satellite rainfall estimates produced using a relatively simple TAMSAT algorithm performed as good as or even better than other satellite rainfall products that use passive microwave inputs and more sophisticated algorithms. There is no substantial difference between the gridded‐gauge and combined gauge‐satellite products over the test area in Ethiopia having a dense station network; however, the combined product exhibits better quality over parts of the country where stations are sparsely distributed.

AutoGate: automating analysis of flow cytometry data - Stephen Meehan; Guenther Walther; Wayne Moore; Darya Orlova; Connor Meehan; David Parks; Eliver Ghosn; Megan Philips; Erin Mitsunaga; Jeffrey Waters; Aaron Kantor; Ross Okamura; et al. (Immunologic Research, 2014)

Cryptic ecology among host generalist Campylobacter jejuni in domestic animals - Samuel K. Sheppard; Lu Cheng; Guillaume Méric; Caroline P. A. de Haan; Ann‐Katrin Llarena; Pekka Marttinen; Ana Vidal; Anne Ridley; Felicity Clifton‐Hadley; Thomas R. Connor; Norval J. C. Strachan; Ken Forbes; et al. (Molecular Ecology, 2014)
Homologous recombination between bacterial strains is theoretically capable of preventing the separation of daughter clusters, and producing cohesive clouds of genotypes in sequence space. However, numerous barriers to recombination are known. Barriers may be essential such as adaptive incompatibility, or ecological, which is associated with the opportunities for recombination in the natural habitat. Campylobacter jejuni is a gut colonizer of numerous animal species and a major human enteric pathogen. We demonstrate that the two major generalist lineages of C. jejuni do not show evidence of recombination with each other in nature, despite having a high degree of host niche overlap and recombining extensively with specialist lineages. However, transformation experiments show that the generalist lineages readily recombine with one another in vitro. This suggests ecological rather than essential barriers to recombination, caused by a cryptic niche structure within the hosts.

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Challenges of satellite rainfall estimation over mountainous and arid parts of east Africa - Tufa Dinku; Pietro Ceccato; Stephen J. Connor (International Journal of Remote Sensing, 2011)

The P2Y12 receptor as a target of antithrombotic drugs - Stephen O’Connor; Gilles Montalescot; Jean-Philippe Collet (Purinergic Signalling, 2011)

Effects of the novel amiodarone-like compound SAR114646A on cardiac ion channels and ventricular arrhythmias in rats - Heinz Goegelein; Patrick Gautier; Alain Roccon; Stephen O’Connor; Hartmut Ruetten (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

On the coupling between vegetation and the atmosphere - Isabella M. Angelini; Michael Garstang; Robert E. Davis; Bruce Hayden; David R. Fitzjarrald; David R. Legates; Steven Greco; Stephen Macko; Vickie Connors (Theoretical and Applied Climatology, 2011)

Screening and confirmatory testing of MHC class I alleles in pig-tailed macaques - Caroline S. Fernandez; Jeanette C. Reece; Uus Saepuloh; Robert De Rose; Diah Ishkandriati; David H. O’Connor; Roger W. Wiseman; Stephen J. Kent (Immunogenetics, 2011)

The impact of acute strenuous exercise on TLR2, TLR4 and HLA.DR expression on human blood monocytes induced by autologous serum - Stephen Booth; Geraint D. Florida-James; Brian K. McFarlin; Guillaume Spielmann; Daniel P. O’Connor; Richard J. Simpson (European Journal of Applied Physiology, 2010)

Interaction between organochlorines and the AHR gene, and risk of non-Hodgkin lymphoma - Carmen H. Ng; Rozmin Janoo-Gilani; Payal Sipahimalani; Richard P. Gallagher; Randy D. Gascoyne; Joseph M. Connors; Jean-Philippe Weber; Agnes S. Lai; Stephen Leach; Nhu D. Le; Angela R. Brooks-Wilson; John J. Spinelli (Cancer Causes & Control, 2010)

MHC class I allele frequencies in pigtail macaques of diverse origin - Bridget F. Pratt; David H. O’Connor; Bernard A. P. Lafont; Joseph L. Mankowski; Caroline S. Fernandez; Retno Triastuti; Andrew G. Brooks; Stephen J. Kent; Miranda Z. Smith (Immunogenetics, 2006)

A Comparison of the Efficacy of Pond-Net and Box Sampling Methods in Turloughs - Irish Ephemeral Aquatic Systems - Áine O Connor; Stephen Bradish; Thomas Reed; James Moran; Eugenie Regan; Marjolein Visser; Mike Gormally; Micheline Sheehy Skeffington (Hydrobiologia, 2004)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

The phosphorylase kinase activity of hearts from phosphorylase kinase-deficient mice - Stephen R. Gross; Joseph J. Connor; Randolph M. Johnson (Biochemical Genetics, 1983)